Pak1 Kinase Promotes Activated T Cell Trafficking by Regulating the Expression of L-Selectin and CCR7 - Dios-Esponera, Ana; Melis, Nicolas; Subramanian, Bhagawat C.; Weigert, Roberto; Samelson, Lawrence E. (Frontiers in Immunology, 2019)
T cell trafficking between the blood and lymphoid organs is essential for the function of the adaptive immune system. Lymphocyte homing to lymph nodes requires that they cross endothelial barriers present in blood vessels and lymphatics. This multi-step process requires a remodeling of the lymphocyte plasma membrane, which is mediated by the dynamic re-arrangement of the actin cytoskeleton. Pak1 plays a central role in cell morphology, adhesion and migration in various cell types. Here we demonstrate that Pak1 is required for activated CD4+ T cell trafficking to lymph nodes. Pak1 deficiency in T cells causes a defect in the transcription of CCR7 and L-selectin, thereby altering lymphocyte trafficking. Additionally, we report an increase in L-selectin shedding in Pak1-deficient T cells, which correlates with a decrease in the recruitment of calmodulin to the cytoplasmic tail of L-selectin during T cell activation. Overall, our findings demonstrate that by regulating the expression of two major lymph node homing molecules, L-selectin and CCR7, Pak1 mediates activated CD4+ T cell trafficking.